ChemInform Abstract: Ba4Ga2Se8: A Ternary Selenide Containing Chains and Discrete Se2‐2 Units. Issue 24 (27th May 2016) - Yin, Wenlong; Iyer, Abishek K.; Lin, Xinsong; Mar, Arthur
Abstract: Ba4 Ga2 Se8 is prepared by solid state reaction of a stoichiometric mixture of BaSe, Ga2 Se3, and Se (evacuated silica tube, 1023 K, 96 h).